The Factors Influencing Poverty Rate in East Java Province - Diandra Ranny Prastiti (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
The development is the most important thing of a country to achieve the welfare. Thewelfare can be achieved if there is a decrease in poverty. The objective of this research isto observe and analyze the factors influencing poverty rate. The dependent variable ofthis research is the percentage of poverty rate and the independent variable are economicgrowth, minimum wage, and unemployment rate. Data that obtained in this research issecondary data from Central Statistical Agency in terms of panel data covering 38districts / cities in East Java province of 2006-2015. The data analysis method is usingthe panel data analysis with Fixed Effect Model Approach. According to this study, theresult stated that the economic growth and minimum wage are significant and has anegative effect to poverty rate, and also unemployment are not significant and havenegative influence to poverty rate.Keyword: Poverty, Economic Growth, Minimum Wage, Unemployment